An Empirical Analysis of the Effect of Deregulation of Money Market Operations on the Performance of the Nigerian Economy - G.D, ISIWU; A.S., OKOH; E.A, OJIYA; A.B., MAMMAN, (International Journal of Scientific Research and Management (IJSRM), 2017)
Financial markets are vital components of the financial system of any nation. The importance of these markets in any modern economy is enormous. It is in the light of the importance placed on money market operations that this study focused on the effect of deregulation of money market operations on the performance of the Nigerian economy. It examined the relationship between GDP vis-à-vis money market instruments namely, Treasury bills (TB), Treasury Certificate (TC), Certificates of Deposit (CD), Commercial papers (CP) and Bankers' Acceptances (BA) in the Nigerian economy for the period 1986 to 2015. Data for the study were analyzed using the OLS multiple regression techniques and empirical estimation was carried out using E-views econometric software version 8.0. The findings show robust evidence of linear relationship.  Results derived from empirical analysis are thought-provoking and a wakeup call for policy makers to get more committed to revitalizing the Nigerian money market for efficiency, effectiveness and more robust activities in the sector.  In concluding, the study holds that there exists a unique longrun equilibrium relationship between money market instruments and economic growth in Nigeria. Similarly, the result show that money market deregulation have significant impact on the performance of the Nigerian economy within the period under reference. The study thus recommended that the Nigerian monetary authorities should initiate policies that would encourage money market operations and also be proactive in CBN surveillance role in order to check practices that could undermine or sabotage market integrity and soundness.  Finally, there is the need for the creation of an enabling (investment friendly) environment by concerned authorities (both government and monetary policy regulators), as it will further deepen the popularity of the instruments and subsequently create market for those instrument(s).